1998
DOI: 10.1029/98jd01807
|View full text |Cite
|
Sign up to set email alerts
|

Ozone climatologies at 9–12 km altitude as seen by the MOZAIC airborne program between September 1994 and August 1996

Abstract: Abstract. From data collected at cruise levels by the five aircraft of the Measurement of Ozone and Water Vapor by Airbus In-Service Aircraft (MOZAIC) program during a 2-year period (September 1994 to August 1996), an accurate ozone climatology at 9-12 km altitude has been generated over the northern hemisphere (130øW -140øE; 0ø-80øN), and down to 30øS over South America and Africa. North of 35øN, the distribution is dominated by the influence of ozone-rich air of stratospheric origin; farther south, ozone-poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 27 publications
1
72
0
1
Order By: Relevance
“…We consider the aircraft measurements during ascent and descent to be vertical profiles even though there is significant (350 km) horizontal travel between the ground and cruising altitude. Comparisons with ozonesondes (which ascend more steeply than aircraft) (Thouret et al, 1998a) and lidar (which provides a two-dimensional coverage of layers) (Stoller et al, 1999) have shown that the assumption is satisfactory. Table 2 gives the number of profiles available over Equatorial Africa since April 1997 as a total and per month.…”
Section: Methodsmentioning
confidence: 97%
“…We consider the aircraft measurements during ascent and descent to be vertical profiles even though there is significant (350 km) horizontal travel between the ground and cruising altitude. Comparisons with ozonesondes (which ascend more steeply than aircraft) (Thouret et al, 1998a) and lidar (which provides a two-dimensional coverage of layers) (Stoller et al, 1999) have shown that the assumption is satisfactory. Table 2 gives the number of profiles available over Equatorial Africa since April 1997 as a total and per month.…”
Section: Methodsmentioning
confidence: 97%
“…O 3 was measured using the dual-beam UV absorption analyzer (Thermo Environment Instruments -Model 49-103), with an overall measurement precision of ±2 ppbv. The sensors were recalibrated after every 500 flight hours (Thouret et al, 1998a. More details of this program can be found on the MOZAIC website (http://mozaic.aero.obs-mip.fr/web/).…”
Section: Mozaic O 3 Data Over Beijingmentioning
confidence: 99%
“…Traditionally, mean profiles averaged by season or year, together with some measure of variability about these means, have been analyzed. Examples of studies that have focused on constructing an ozone climatology for particular locations, include Kirchhoff et al (1991), Diab et al (1996), Fortuin and Kelder (1998), Thouret et al (1998a), Logan (1999) and Thompson et al (2003). However, computation of the mean tends to obscure the profile micro-structure because of the many counteracting influences present in the data.…”
Section: Introductionmentioning
confidence: 99%